Design and crashworthiness analysis of novel gradient hashtag-shaped fractal thin-walled structure - Jiale Huang; Haoke Zhou; Wenqi Huang; Yuxin Zhang; Guoda Du; Wentian Lu; Xinmei Xiang; Jingren Gou (Materials & Design)
Inspired by the fractal and hierarchical features of organisms, a novel hashtag-shaped fractal structure (#-FS) was proposed, and its crashworthiness performance was analyzed using finite element simulations. The results show that the proposed #-FS exhibits superior energy-absorbing capacity compared to the conventional square tube under the same mass condition. Compared with conventional square tube, the energy absorption of #-FS with 3rd level increases by 216.36 % and its peak crush force (PCF) decreases by 0.24 % at the same mass. Finally, the effects of the wall thickness gradient (k) on the crashworthiness performance of #-FS and the hashtag-shaped gradient fractal core structure (#-GFS-k-SW) were systematically investigated.